2005
DOI: 10.1111/j.1468-2982.2005.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pre-Headache Phases and Trigger Factors of Migraine and Episodic Tension-Type Headache: Do they Share Similar Clinical Pathophysiology?

Abstract: Trigger factors, signs and symptoms of the preheadache phases of episodic tension-type headache (ETTH), typical aura with non-migraine headache (TANMH), migraine with (MA) and without aura (MwA) may show similar features. Our objective was to investigate the preheadache phases and trigger factors of these headache types. Questionnaires including trigger factors, signs and symptoms of preheadache phases were answered by all headache patients. A total of 96 patients, 31 ETTH, nine TANMH, 23 MA and 33 MwA patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 23 publications
7
97
0
1
Order By: Relevance
“…Several studies are consistent with stress, lack of sleep, and fasting being the most common trigger factors 3,4 , but some other factors such as including alcohol intake, excessive caffeine consumption, and hormonal factors in women are also recognized. In spite of its importance, little is known about migraine trigger factors in our society.…”
Section: Fatores Desencadeantes De Enxaquecamentioning
confidence: 80%
“…Several studies are consistent with stress, lack of sleep, and fasting being the most common trigger factors 3,4 , but some other factors such as including alcohol intake, excessive caffeine consumption, and hormonal factors in women are also recognized. In spite of its importance, little is known about migraine trigger factors in our society.…”
Section: Fatores Desencadeantes De Enxaquecamentioning
confidence: 80%
“…Most studies support the relationship between migraine and alcohol consumption, which is considered a major trigger factor of migraine attacks 1,2,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21 . However this relationship is complex and depends on many factors.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, these factors have been identified as precipitating factors for migraine due to estrogen effect. 19,26 In our study, the sleep quality of probable migraineurs was found significantly lower than the healthy participants. Incidence of sleep disorders was determined higher in migraine patients than general population in the study which conducted by Peres et al 28 Sleep disorders may be a symptom which associated with migraine.…”
Section: Discussionmentioning
confidence: 43%
“…Karli et al have been reported that smoking is the one of the most prominent precipitating factors of migraine type headaches. 26 It was known that carbon monoxide intoxication had been associated with headache. Also inhalation of tobacco smoke, which contains up to 5% carbon monoxide, raised the plasma carboxyhemoglobin level.…”
Section: Discussionmentioning
confidence: 99%